PENYULUHAN PEMANFAATAN KAIN PERCA PADA SANTRIWATI PONPES SAYYID IBRAHIM MADINA AL MUNAWAROH DESA PERKEBUNAN MARPINGGAN - Butar-Butar, Khairunnisa; hasibuan, elfi; dwi meilasari, retno (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
Fabric waste is inorganic waste which continues to increase every year due to the rapid pace of adult fast fashion. The United States Environmental Protection Agency (US EFA) launched that 5% of the world's land is covered by textile waste that cannot be recycled and is decomposed with an increase of 3% to 5% every year (Munir et al., 2021). If there is an increase from year to year, of course this will pollute the earth. Therefore, patchwork waste must be recycled into creative products that have an economic selling value such as hair ties and brooches. In addition to reducing earth pollution due to textile waste, the waste recycling process becomes a creative product with selling value. This community service aims to increase the creativity and economy of the community. The method used in this service is demonstration and practice, by giving examples of how to make hair ties and brooches from patchwork. Based on the activities that have been carried out, the results are obtained that the students are enthusiastic about the activities and want similar activities in terms of making crafts or other products. The results of the evaluation felt that the activity was very useful and could increase knowledge about the use of goods around and including obtaining economic income for students and Islamic boarding schools.